Glucosamine sulfate suppresses the expression of matrix metalloproteinase-3 in osteosarcoma cells in vitro. Issue 1 (December 2016) - Pohlig, Florian; Ulrich, Jörg; Lenze, Ulrich; Mühlhofer, Heinrich; Harrasser, Norbert; Suren, Christian; Schauwecker, Johannes; Mayer-Kuckuk, Philipp; von Eisenhart-Rothe, Rüdiger
Abstract Background Glucosamine, a common dietary supplement, has a possible anti-sarcoma effect. However, an understanding of the underlying mechanism of such an effect is limited. For this study we hypothesized that glucosamine suppresses the basal level of matrix metalloproteinase expression in human osteosarcoma cell lines. Methods We examined the osteosarcoma cell lines, MG-63 and SaOS-2. Cells were exposed to 0, 10, 50 and 100 μg/ml glucosamine sulfate for 48 h and treatment toxicity was determined through measurement of cell viability and proliferation. Relative gene expression of matrix metalloproteinase (MMP)-2, -3 and -9 was quantified by real-time polymerase chain reaction. Protein levels of MMP-2 and -9 were assessed by ELISA. Results Administration of 10, 50 or 100 μg/ml glucosamine sulfate had no effect on the cell viability of MG-63 and SaOS-2 cells. A significant reduction of MMP expression in both cell lines was observed only for MMP-3, while a decrease in MMP-9 was seen in SaOS-2 cells. The expression of MMP-2 was not significantly affected in either cell line. Protein level of MMP-3 was reduced in both cell lines upon stimulation with 10 μg/ml glucosamine sulfate whereas for MMP-9 a decrease could only be observed in SaOS-2 cells. Conclusion In this study, we found a pronounced suppressive effect of glucosamine sulfate particularly on MMP-3 and also MMP-9 mRNA and protein levels in osteosarcoma cell lines in vitro. The data warrants further investigations into the potential anti-tumor efficacy of glucosamine sulfate in osteosarcoma.